2016
DOI: 10.18632/oncotarget.10913
|View full text |Cite
|
Sign up to set email alerts
|

Inherent low Erk and p38 activity reduce Fas Ligand expression and degranulation in T helper 17 cells leading to activation induced cell death resistance

Abstract: Activation Induced Cell Death of T helper cells is central to maintaining immune homeostasis and a perturbation often manifests in aberrant T helper cells that is associated with immunopathologies. Significant presence of T cells positive for IL-17A (Th17) and dual positive for IFN-γ/IL-17A (Th1/Th17) in both effector (CD45RA+RO+) and memory (CD45RA−RO+) compartments with differential FasL protein in RA peripheral blood suggested their differential TCR AICD sensitivity. Lowered active caspase-3 in Th17 and Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our previous work on CD4 þ T cells from the peripheral blood of rheumatoid arthritis patients demonstrated that an inherently low MAPK activity, particularly ERK1/2, protects Th17 cells from AICD. 26 We could validate those results in TBU, because we found that ERK1/2 activity was significantly lower in the autoreactive T cells compared with the ESAT-6-specific population (Figs. 5A, 5B).…”
Section: Retinal Antigen-specific Cells Are Resistant To Aicdmentioning
confidence: 54%
“…Our previous work on CD4 þ T cells from the peripheral blood of rheumatoid arthritis patients demonstrated that an inherently low MAPK activity, particularly ERK1/2, protects Th17 cells from AICD. 26 We could validate those results in TBU, because we found that ERK1/2 activity was significantly lower in the autoreactive T cells compared with the ESAT-6-specific population (Figs. 5A, 5B).…”
Section: Retinal Antigen-specific Cells Are Resistant To Aicdmentioning
confidence: 54%
“…As shown by Song et al, pore formation by alpha-toxin allows Ca 2+ ions to enter the cell and induce downstream signaling (39), which could explain the abovementioned cytokine production upon stimulation of human T cells with sublytic concentrations of alpha-toxin (22,23). In the same line, enhanced Ca 2+ signaling might result in increased activation-induced cell death in Th1 cells, as these cells were reported to be more susceptible to Ca 2+ signaling when compared to Th17 cells due to differential Fas ligand and c-FLIP expression as well as activity of p38 and ERK (40)(41)(42). Interestingly, we could mimic the differential effects of alpha-toxin on Th1-and Th17-polarized cells using Ionomycin, suggesting an increased susceptibility toward Ca 2+ signaling in Th1 cells as mechanism underlying the differential susceptibility toward alpha-toxin-induced cell death.…”
Section: Discussionmentioning
confidence: 96%
“…The Fas/FasL pathway, also known as the death receptor pathway, acts as an apoptotic signaling receptor, forming a death-inducing complex by binding to its ligand FasL and activating its downstream caspase-3 to induce apoptosis [ 37 ].…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%